2016
DOI: 10.21037/jss.2016.04.01
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and surgical outcomes of an intramedullary C2 spinal cord cavernoma: a case report and review of the relevant literature

Abstract: Background:The spinal cord intramedullary cavernoma (SCIC) is a rare form of hemangioma that typically behaves as a space-occupying lesion resulting in neurological symptoms, including bladder and bowel dysfunction. To date, there have been few reports characterizing the clinical presentations and surgical outcomes of cavernomas at the C2 spinal level or the potential for resolution of bladder and bowel symptoms postoperatively. This case details the clinical course of a patient with a C2 cavernoma with an aty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…10,12 Across 23 literature studies with 825 patients, 671 CMs (81%) were totally resected. 3,7,9,[10][11][12]16,[17][18][19][24][25][26]28,29,32,34,[36][37][38][41][42][43] Transient early postoperative morbidity was reported in 15 out of 116 patients (12%) in 3 series, At the long-term followup 224 patients were improved (27.15%), 393(47.5%) were unchanged, and 72 (8.7%) were worsened, as compared with their preoperative status. These overall results are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…10,12 Across 23 literature studies with 825 patients, 671 CMs (81%) were totally resected. 3,7,9,[10][11][12]16,[17][18][19][24][25][26]28,29,32,34,[36][37][38][41][42][43] Transient early postoperative morbidity was reported in 15 out of 116 patients (12%) in 3 series, At the long-term followup 224 patients were improved (27.15%), 393(47.5%) were unchanged, and 72 (8.7%) were worsened, as compared with their preoperative status. These overall results are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 91%
“…Outcome on surgically treated SICM 3,7,9,[10][11][12]16,[17][18][19][24][25][26]28,29,32,34,[36][37][38][41][42][43]…”
Section: Tablementioning
confidence: 99%
“…Bladder involvement occurs in about 11–35% of patients with spinal CM [8, 11]. Although Kivelev et al [11] in their adult series reported no change in the bladder function after surgery, others have shown improvement [12, 13]. In children, the rate of recovery appears to be better which is probably related to plasticity of neural tissue [4, 6, 14].…”
Section: Discussionmentioning
confidence: 99%